Tumor-Associated Antigens in Rheumatoid Arthritis Interstitial Lung Disease or Malignancy? - Gökhan SARGIN,; Reyhan KÖSE,; Taşkın ŞENTÜRK, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the serum tumor-associated antigen levels and the possible association between these markers and interstitial lung disease (ILD) or malignancy in rheumatoid arthritis (RA) patients. Patients and methods: The study included 83 RA patients (20 males, 63 females; mean age 59.3±12.1 years; range 25 to 83 years), 43 with ILD (13 males, 30 females; mean age 60.1±11.5 years; range 25 to 83 years) and 40 without ILD (7 males, 33 females; mean age 58.5±12.7 years; range 28 to 78 years). Clinical symptoms, pulmonary function test, chest X-ray, and high-resolution computed tomography were used for the diagnosis of ILD. Age, sex, history of smoking, acute-phase reactants, rheumatoid factor, anti-cyclic citrullinated peptide, carcinoembryonic antigen, cancer antigen (CA) 15-3, CA 125, and CA 19-9 were evaluated. The relationship between parameters in RA patients with/without ILD was assessed by t-test and Mann-Whitney U test. Results: Five RA patients (11.6%) with ILD had carcinoembryonic antigen levels above the upper limit. The numbers of RA-ILD patients with above the upper limit of CA 19-9, CA 15-3, and CA 125 levels were 10 (23.2%), 13 (30.2%), and five (11.6%), respectively. Rates of RA patients without ILD with tumor-associated antigens exceeding the upper limit were 15% for carcinoembryonic antigen, 2.5% for CA 19-9, 7.5% for CA 15-3, and 7.5% for CA 125. No evidence of any malignancy was detected by medical history, physical examination, and laboratory and imaging methods in patients who had high levels of serum tumor-associated antigen. CA 15-3 (p=0.001), CA 125 (p=0.040), and CA 19-9 (p=0.018) levels were statistically significantly different in RA patients with ILD compared to those without ILD. Rheumatoid factor, anti-cyclic citrullinated peptide, and tumor-associated antigens were higher in RA patients with ILD than those without ILD. Conclusion: There is a relationship between ILD and tumor marker levels in connective tissue diseases. Elevated tumor markers may not be associated with hidden tumor or malignancy in RA patients. These antigens may be used as predictive biomarkers particularly in RA patients with ILD.